Abolition of Capital Punishment in India: The Need of the Hour - Humd, Sana; Umar, Dr. Haris; Khan, Dr. Mohd Wazid (Society & Sustainability, 2022)
This article is concerned with the penological perspective of capital punishment in India. It critically examines the contentious views of honorable courts, policymakers, commentators, human rights activists, and the Law Commission of India on whether capital punishment should be abolished or retained as earlier or whether there should be some alternative to it as it is practiced in other nations. In so doing, It has analyzed the penal provisions of different enactments provided in favor of Capital Punishment in India, including a critical examination of the lacuna in the enforcement and implementation of the death penalty. This article has referred to the contradictory landmark judgments of the hon'ble Courts of India. This article reviews the suggestions made by the Law Commission of India in its 262nd Reports to determine whether legislators have considered them for future adoption. It has also discussed the theories advocating capital punishment as well as systems of capital punishment in other countries.